(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Compression garments apply pressure to the body to provide health benefits, such as increasing the blood circulation, shaping the body and supporting healing after medical procedures. Fabrics used for compression garments are elastic, and the amount of fabric stretching and the ability of maintaining the stretching force are directly related to the compression effectiveness. However, there is currently little information about the fabric and its mechanical properties, and there is a demand from compression garment manufacturers to better understand the fabric properties and their serviceability. This paper studied the physical and mechanical properties of 4 Nylon/Spandex knitted fabrics as commercial medical compression garments. In particular, fabric elasticity and bursting strength were examined to demonstrate the applicability of the fabrics for providing satisfactory compression. It was observed that the compression garment fabrics had an open knitted structure with stable dimensions, and Spandex was only present in the wale direction. Tensile assessment revealed that the compression fabrics were strong and their breaking extension was well beyond 200%. The fabric stretching force had a near linear relationship with its elongation when the fabric was stretched upto 100% extension. After fatigue stretching, the average immediate recovery of compression fabrics examined was more than 95% and the average elastic recovery after an extended period of relaxation was at least 98%. High fabric bursting strength and compression extension were also found. The results of fabric physical and mechanical properties from this study are very important for understanding whether a fabric is suitable for engineering compression garments, and also for estimating the required compression force for designing an individualised compression garments with the medical compression fabrics.